2015
DOI: 10.1038/jp.2014.241
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of umbilical cord blood cell developmental changes and reference ranges by gestation, gender and mode of delivery

Abstract: Reference ranges were established for cord blood. Erythroid and myeloid cells show developmental changes. Mode of delivery has a significant effect on hematologic values. Only a rare parameter showed differences based on gender. The cord blood complete blood cell count has the potential for providing relevant clinical information for managing neonatal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 18 publications
9
33
2
3
Order By: Relevance
“…Both methods gave distributions ranging from negligible content of less than 1%, to very high values up to 55%. Proportions of NRBC in cord blood are reported to vary between 0 and 25% of total cells , but some authors have also reported content higher than 25% . The distribution obtained with the flow cytometry method is in agreement with these reports, as close to 99% of the qualified CBU showed NRBC content in this range.…”
Section: Discussionsupporting
confidence: 85%
“…Both methods gave distributions ranging from negligible content of less than 1%, to very high values up to 55%. Proportions of NRBC in cord blood are reported to vary between 0 and 25% of total cells , but some authors have also reported content higher than 25% . The distribution obtained with the flow cytometry method is in agreement with these reports, as close to 99% of the qualified CBU showed NRBC content in this range.…”
Section: Discussionsupporting
confidence: 85%
“…The impact of mode of delivery on immune development is incompletely understood. Furthermore, while mode of delivery does impact absolute numbers of cord blood monocytes, differences in PRR‐stimulated neonatal monocyte/mononuclear cells responses have not been attributable to mode of delivery in most studies . Interestingly, the one infant with chorioamnionitis‐exposure that did not cluster with the others within the principal component analysis, exhibited the lowest grade of chorioamnionitis, suggesting a potential dose effect on monocyte responses.…”
Section: Discussionmentioning
confidence: 95%
“…The following blood parameters were recorded [with our newborn laboratory reference values]: erythrocyte count ([4.5–6.2] T/L), hemoglobin concentration ([16–20] g/dL), hematocrit ([50–60] %), mean corpuscular volume MCV ([95–110] fL), total leukocyte count ([7–26] G/L), differential leukocyte count, comprising neutrophil [1.5–28], eosinophil [0–0.4], basophil [0–0.1], lymphocyte and monocyte counts [0–1.5] (G/L), and platelet count ([150–400] G/L).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristic changes in reference pediatric blood parameters during the first years of life have been extensively studied . With regard to term newborns, these physiological variations have been investigated at birth , during the first hours and first week of life, and up to 6 months of age . Physiological data concerning preterm neonates are more fragmentary, yet these infants are particularly likely to require transfusions or anti‐infective treatments that are modulated according to blood counts.…”
Section: Introductionmentioning
confidence: 99%